Draught, Fish, and Presence: Teaching Semi-Arid Ecology with a CAVE - Nobrega, João Anísio Marinho Da; Renno-Costa, Cesar; Araújo, Magnólia; Souza, Alyson Matheus De Carvalho (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Brazil’s north-eastern Sertão is shaped by erratic rainfall, ephemeral streams and prolonged drought, which reveal fragile hydrological pulses that static exhibits cannot convey: the rise and fall of water levels, the transient flow of waterways or the behavioural responses of fish to flood and drought. To address this, we created "Peixes do semiárido: Nadando no Seco" ("Semiarid Fish: Swimming in the Dry"), a four-wall-plus-floor CAVE installation that immersively portrays the entire aquatic cycle of the Açude Gargalheiras reservoir and the life-history strategies of five representative species (Prochilodus brevis, Leporinus piau, Hoplias malabaricus, Oreochromis niloticus and Cichla sp.). A 250-second pre-rendered film cycles through four ecological phases (Dry Night → Rain Inundation → Flood Life → Return to Drought) while a finite-state controller synchronises spawning, burrowing and mortality behaviours. An offline rendering-to-projection pipeline bypasses the 15 fps limit of live streaming, delivering seamless 3270 × 4500 px edge-blended imagery across five surfaces. By privileging passive observation—a deliberate design choice to enhance focus on complex ecological narratives—the exhibit reduces cognitive load, fits curator-staffing constraints and fosters situated learning. Grounded in regional ichthyological research, this reproducible, low-maintenance VR framework offers small and mid-sized museums a scalable model for high-fidelity environmental education. An online visitor survey (N=38) provided strong validation for the approach’s effectiveness in engagement and conveying hydrological dynamics, though participants suggested that more explicit cues could further enhance both the experience and its pedagogical impact.